Labor Migration in Taiwan - Lin, Ji-Ping (My University, 1998)
This thesis consists of three parts. The first part (Chapter 3) is to achieve a comprehensive understanding of the interrelationships among migration, the evolution of the settlement system, and the socioeconomic development in Taiwan over the past four hundred years (1600-1990), with an emphasis on the impacts of developmental strategy and government policy. The major finding is that the migration process in Taiwan appears to be highly responsive to the changing socioeconomic context.
The second part (Chapter 4-6) involves the studies of (1) life-time migrations and (2) 1985-90 primary, return, and onward migrations of the labor force in Taiwan, based on the 1990 Taiwanese census. The main theme of these analyses is to assess the responsiveness of labor migration to the labor market forces and to the economic restructuring and globalization that took place in the 1980s. The main findings are (1) that primary labor migration played a much greater role than did onward and return labor migrations in affecting the transfers of human resources and (2) that the three types of labor migration responded in a rational way to the effects of patriarchal value system, educational attainment, location-specific capital, market forces, and economic restructuring and globalization.
The third part (Chapter 7) is devoted to the analysis of the behaviors of fast repeat labor migration in Taiwan, based on the linked migration data. The main findings are (I) that the most important factors of fast repeat migrations turned out to be the chronicity and patriarchal ideology, (2) that those with a limited labor market knowledge and an unsuccessful job search are more prone to make a fast return migration, and (3) that the more experienced and more successful previous migrants are more prone to make a fast onward migration.
Keywords: Geography and Geology; Geology; Geology